Enzymatic production of cassava flour using pectinase - Prakash, Nagasvara Ravo (2014)
This paper presents the studies of enzymatic activity of pectinase enzyme in liberation of starch from cassava (Manihot esculenta), especially in cassava flour. The starch granules in cassava is hold up by pectin molecules, in which its cell wall can be broken by pectinase enzyme activity. Hence, the assumption is made where the amount of starch released is inversely proportional to amount of pectin molecules left after the enzyme activity. The experiment was designed to determine the optimum condition for the pectinase activity, where parameter of incubation time, temperature, pH of the solution and concentration of enzyme is taken into consideration. The final product, which is the dried cassava powder (flour) is analyzed for equivalent pectin weight by titration method. The flour produced based on optimum conditions was then analyzed for its nutritional content. Analysis of total protein content, moisture content, ash content, crude fat content, crude fiber content were carried out. Based on the experiment, it is found that the optimum condition for pectinase activity is at between 45-50°C temperature, 7 hours of incubation time, pH value of 5 and concentration of 20 mg/ml. At these conditions, the increase in starch release is about 6%, where this value could be higher when more detailed starch assay is carried out. The nutritional profile is also satisfactory, in some cases, very healthy profile, which means the cassava flour fermented with pectinase enzyme have high potential to replace wheat flour.